Pengembangan Buku Suplemen Matematika (SUKA) untuk Penanaman Konsep Bangun Datar Siswa Sekolah Dasar - Asfi Manzilatu Rohmah; Ida Putriani; Desy Dwi Riana (Musamus Journal of Primary Education, 2021)
Learning mathematics in elementary schools has many shortcomings in terms of learning resources so that effective learning resources are needed to support teaching and learning activities. The purpose of this study is to produce appropriate learning products. This research and development uses the Borg n Gall model with 7 adapted development steps, namely: potential and problems, data collection, product design, design validation, design revision, product testing, product revision. The results of the percentage of validation from the 3 validators are: (1) 90.5% of material experts (2) 85% of language experts and (3) 82% of material experts. The results of the student readability questionnaire showed that the supplement book was feasible to use with a reading percentage of 94% and a positive response from students to the book. The teacher readability rate showed a reading percentage of 90% was suitable for use. So, the mathematics supplement book developed can be used in the learning process.